HOXB1 founder mutation in humans recapitulates the phenotype of Hoxb1−/−mice - Webb, Bryn D.; Gaspar, Harald; Camminady, Anne (The American journal of human genetics, 2012)
Members of the highly conserved homeobox (HOX) gene family encode transcription factors that confer cellular and tissue identities along the antero-posterior axis of mice and humans. We have identified a founder homozygous missense mutation in HOXB1 in two families from a conservative German American population. The resulting phenotype includes bilateral facial palsy, hearing loss, and strabismus and correlates extensively with the previously reported Hoxb1−/− mouse phenotype. The missense variant is predicted to result in the substitution of a cysteine for an arginine at amino acid residue 207 (Arg207Cys), which corresponds to the highly conserved Arg5 of the homeodomain. Arg5 interacts with thymine in the minor groove of DNA through hydrogen bonding and electrostatic attraction. Molecular modeling and an in vitro DNA-protein binding assay predict that the mutation would disrupt these interactions, destabilize the HOXB1:PBX1:DNA complex, and alter HOXB1 transcriptional activity.